Phoebe the moonlight dragon - Mara, Maddy (Mara, Maddy. Dragon girls, 2022)
"Phoebe has a special task ahead of her. She must spread her wings and rescue the Dreamlets, magical creatures who create dreams for all the forest animals. Can Phoebe overcome her fear of the dark to help save nighttime?"--